2010
DOI: 10.1111/j.1600-048x.2010.05058.x
|View full text |Cite
|
Sign up to set email alerts
|

Loop migration in adult marsh harriers Circus aeruginosus, as revealed by satellite telemetry

Abstract: Loop migration among birds is characterized by the spring route lying consistently west or east of the autumn route. The existence of loops has been explained by general wind conditions or seasonal differences in habitat distribution. Loop migration has predominantly been studied at the population level, for example by analysing ring recoveries. Here we study loop migration of individual marsh harriers Circus aeruginosus tracked by satellite telemetry. We show that despite a generally narrow migration corridor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
81
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 15 publications
(23 reference statements)
8
81
0
Order By: Relevance
“…For example, we can now observe broadscale divergence in migration patterns, which can add to our current understanding of how phenotypes are structured at macro scales (Jetz et al 2009) and the role of migration in structuring avian evolution. In addition, hypotheses that address observed variation in migratory patterns can be tested from a broader perspective; e.g., the role of atmospheric conditions and stopover habitat as factors responsible for defining seasonal variation in migration routes that results in looped trajectories (Klaassen et al 2010). Building on these examples, an improved understanding of the spatiotemporal structure and drivers of migration at macro scales can better inform conservation strategies directed toward the broadscale maintenance of genetic diversity and the quality of stopover habitats.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we can now observe broadscale divergence in migration patterns, which can add to our current understanding of how phenotypes are structured at macro scales (Jetz et al 2009) and the role of migration in structuring avian evolution. In addition, hypotheses that address observed variation in migratory patterns can be tested from a broader perspective; e.g., the role of atmospheric conditions and stopover habitat as factors responsible for defining seasonal variation in migration routes that results in looped trajectories (Klaassen et al 2010). Building on these examples, an improved understanding of the spatiotemporal structure and drivers of migration at macro scales can better inform conservation strategies directed toward the broadscale maintenance of genetic diversity and the quality of stopover habitats.…”
Section: Discussionmentioning
confidence: 99%
“…For birds, geographical wind patterns have a most important effect on the evolution of migration routes [9][10][11][12]. However, little is known about how individual birds respond to lateral wind drift during migration (reviews in [2,5,13]).…”
Section: Introductionmentioning
confidence: 99%
“…Although most published studies of bird migration have focused on fall, some studies have presented spring migration data and compared the details of spring vs. fall migration (e.g., Klaassen et al 2010). Martell et al (2004) reported on spring and fall migration of seven ospreys that migrated from Florida to South America and Alerstam et al (2006) found differences in spring and fall migration strategies among seven Ospreys tagged in Sweden.…”
Section: Migració N Primaveral De Individuos Adultos De Pandion Haliamentioning
confidence: 99%